A review and meta-analysis of remote sensing data, GIS methods, materials and indices used for monitoring the coastline evolution over the last twenty years. Issue 1 (1st January 2021) - Apostolopoulos, Dionysios; Nikolakopoulos, Konstantinos
ABSTRACT: The current review study focuses on a statistical analysis (Meta-analysis) of the most common methods, materials, software, and indices used by researchers over the last twenty years to evaluate and quantify the shoreline evolution. Furthermore, this review targets to highlight some critical points through studied literature such as a) the low rate of high-resolution satellite images usage in a subject where the accuracy is prerequisite, b) the effort to derive information from Landsat images in order to take advantage of the 50-years archive and the freely availability c) the impulse of the UAV during the last 5 years as an alternative low cost but high accurate source of data d) the fact that only 50% of the coastal erosion studies are funded. One hundred thirty-eight papers and articles have been analyzed in detail by the authors and all the key points (methods, materials, software, and indices) were sorted for further statistical analysis. This study is not intended to criticize neither the methods nor the results being mentioned in the previous studies but to give the opportunity to the researchers (especially the new ones) to have an overall view of the subject for the last 20 years with just a glimpse.